Sustainability reporting: profile of large brazilian companies according to the Global Reporting Initiative standard (Gestão & Regionalidade, 2024)
Studies show that, currently, sustainability is one of the strategies used by many organizations to accomplish their core business. To meet their objectives, organizations need instruments that publicize their sustainable actions. In this context, the sustainability report is an important tool that indicates the social, economic and environmental factors of the organizations, with greater transparency. Considered the main communication instrument on sustainable performance, the Global Reporting Initiative (GRI) guidelines allow organizations to externalize their actions in the environmental, social and economic dimensions. The aim of this work is to examine sustainability reports from major Brazilian companies in order to verify the institutional profile according to the Global Reporting Initiative (GRI) standard and, based on the respective parameters, to perform a critical analysis of sustainable practices. The research is qualitative, exploratory, documental and transversal. The results of the research indicate that, among the institutionalized sustainable objectives, many have been achieved. However, it can be seen that there are still challenges to be faced by organizations, especially regarding the environmental dimension, which is the basis of social and economic relations.
Keywords: Sustainability; Sustainable Development; Large Companies; Sustainability Reports; Indicators; GRI